Advances in Cellular Therapy for T-Cell Prolymphocytic Leukemia - Varadarajan, Indumathy; Ballen, Karen (Frontiers in Oncology, 2022)
T-PLL is a rare, aggressive Hematologic malignancy with a poor prognosis. Alemtuzumab (Campath) remains the cornerstone for treatment with an 80% complete response (CR). Hematopoietic stem cell transplant (HSCT) is considered standard of care as consolidative therapy in eligible patients. However allogeneic stem cell transplant is also complicated by increased rates of infections from chemotherapy, acute Graft vs Host Disease (GVHD), and chronic GVHD. This review aims to report the available literature on the efficacy and complications of consolidative HSCT. It also discusses the importance of patient selection, pre and post-transplant complications including atypical infections and GVHD.